Key Drivers of Profitability in Indonesian Sharia Banks: Faktor Utama Profitabilitas Bank Syariah di Indonesia - Septiani, Neli; Rahmawati , Imelda Dian (Indonesian Journal of Law and Economics Review, 2024)
Background: The banking sector significantly contributes to Indonesia's economic growth, with profitability serving as a key measure of performance and credibility, particularly in sharia banking. Knowledge Gap: Despite the importance of factors like Financing to Deposit Ratio (FDR), Operating Expense to Operating Income (BOPO), and Non-Performing Financing (NPF), their combined impact on profitability in Islamic banking remains underexplored. Aims: This study examines the influence of FDR, BOPO, and NPF on the profitability of Indonesian sharia banks. Methods and Results: Using data from 11 sharia banks listed on the Indonesian Stock Exchange (2018–2022) and multiple linear regression analysis, the study finds FDR and NPF have no significant effect, while BOPO negatively impacts profitability, emphasizing the importance of operational efficiency. Novelty and Implications: This study highlights the critical role of prudential and efficient financial management in Islamic banking, offering insights for enhancing profitability and resilience in Indonesia's sharia banking sector. Highlight : BOPO significantly impacts profitability, highlighting the need for operational efficiency in sharia banking. FDR and NPF show no significant influence on profitability, indicating other factors may play a role. Prudential financial management is crucial for enhancing resilience and growth in Islamic banks Keywords: Sharia banking, profitability, FDR, BOPO, NPF